Pembuatan E-Modul Berbasis Problem Based Learning pada Materi Fluida untuk Memfasilitasi Science Explanation Skill Siswa - Hasanah, Annisa Nurul; Festiyed, Festiyed; Desnita, Desnita; Suherman, Dea Stivani (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop a Problem Based Learning (PBL) based e-module on fluid materials to facilitate students' science explanation skills. This skill is essential to help students construct knowledge, connect scientific concepts, and present understanding logically and based on evidence. The method used in this study is Research and Development (R&D) with the Dick & Carey development model. The limited trial subjects are high school grade XI students with a total of 30 participants. The validation results by material and media experts showed that the e-module is feasible to use with very good quality. Field trials indicate that the e-module is capable of improving students' abilities in explaining fluid concepts scientifically. Thus, this PBL-based e-module is effective as an alternative learning media that supports the strengthening of 21st-century science skills, particularly the ability to explain scientifically.